MODEL OPTIMALISASI DAYA SAING DAN SINERGIVITAS KINERJA UMKM DI JEPARA - Sarwido - -; Dwi Retno Sulistyawati (Spektrum Industri, 2015)
Handling this issue for SMEs remains piecemeal and not comprehensive, comprehensive and simultaneous. Lack of coordination between agencies related to SME development led to many SMEs entangled bad credit and even go out of business. While the existence of SMEs is very important in supporting the national economy and create jobs and prosperity. This study is based on the problems faced by SMEs over the years, both the problems associated with the condition of internal and external conditions, among others, field operations, processing, marketing, capital, human resources, technology, business climate or competition . This research can generally be concluded that based on the results obtained support the hypothesis testing positive and significant that reinforce the concept that SME performance improvement can be achieved through internal factors, external factors, barriers to innovation and partnership capabilities. Although the magnitude of the effect is not the same but overall indicate a significant influence. Keywords : Internal and External Factors, Capability, Obstacles, Performance of SMEs.